Design and optimization of a solar-powered water pumping system for irrigation and water storage purpose - Tanvir, Md. Shahrior; Badhon, Minhazur Rahman; Islam, Shaeera Tasfia; Hasan, Md. Samid Bin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.